2015
DOI: 10.1016/j.exer.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the mammalian limbal stem cell niche

Abstract: Although the existence of the limbal stem cell (LSC) niche is accepted, precise knowledge of its three-dimensional (3D) architecture remains incomplete. The LSC niche was explored on freshly excised and organ-cultured corneoscleral rims from human donors (n = 47), pigs (n = 15) and mice (n = 27) with full-field optical coherence microscopy (FFOCM). Limbal crypt features were detected in 90% of organ-cultured human corneoscleral rims, extending between the palisades of Vogt as radially oriented rectangular (74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 41 publications
3
57
0
1
Order By: Relevance
“…The palisades of Vogt have been used by many other studies for determining the location of the junction between the corneal and conjunctival epithelium. 17,18 In sections of DiI-labeled corneas, we observed that the fluorescent label terminated within this transitional area. As shown in Figure 2B, the DiI label terminates within the epithelial layer (arrow), just lateral to the end of Bowman's layer (arrowhead and dashed line).…”
Section: Resultsmentioning
confidence: 79%
“…The palisades of Vogt have been used by many other studies for determining the location of the junction between the corneal and conjunctival epithelium. 17,18 In sections of DiI-labeled corneas, we observed that the fluorescent label terminated within this transitional area. As shown in Figure 2B, the DiI label terminates within the epithelial layer (arrow), just lateral to the end of Bowman's layer (arrowhead and dashed line).…”
Section: Resultsmentioning
confidence: 79%
“…The thickness of limbal epithelial layer is about 20 µm in both strains, which is account for 50 or 37% of thickness of central corneal epithelium in C57BL/6 or BALB/c mice, respectively 34 . The findings were supported with full-field optical coherence microscopy by Grieve et al ., who detected the palisades of Vogt with limbal crypt features in organ-cultured human corneoscleral rims, but not in fresh mouse cornea, where the limbal region contained only an epithelial trough circumferentially surrounding the cornea 35 .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, using high NA objectives enabled us to rely on both the spatial optical sectioning, and the temporal optical sectioning [3]. Using this setup, structures invisible in FF-OCM were revealed [93,94]. With this multimodal setup, we have been able to add specific contrast to the structural FF-OCT image: Fig.…”
Section: En Face Fluorescence and Coherence Microscopymentioning
confidence: 85%